Plastering work using pump / Muhammad Hazwan Miden - Miden, Muhammad Hazwan (Universiti Teknologi MARA, Perak, 2013)
This report briefly described more about how the plastering pump is use in the project. It is the research and study based on the five months experience at the project site. This report is divided into sections and start with the company background and the background of the construction project. There are many research method as I used to get some knowledge that is related to my report. This report plastering using pump is actually use for plastering work for building more than four storey but in this project the plastering pump is use although it is just one bungalow. So, why the plastering is used in this project? How it works on site? Therefore, this report will described everything and some suggestion which situation the plastering pump is use. As a conclusion, this report will explain in more detail about the process of plastering pump method and procedure to readers.